Bimbingan Teknis Penyusunan Laporan Keuangan Desa Suka Ramai Atas Kecamatan Wih Pesam Kabupaten Benar Meriah - Mangkuwinata, Sonny M. Ikhsan; Haryani, Haryani; Mangkuwinata, Denny Sumantri; Zahara, Mutiara; Akbar, M.; Ulhusni, Annisa (LPPM Umuslim, 2024)
Accountability is control over all activities of village officials in managing village funds, and is an important factor in being accountable for managing village funds. The realization of accountability in village fund management cannot be separated from the competence it has so that the implementation of its duties and obligations can be carried out effectively, efficiently and professionally. In this regard, a group of Development Economics lecturers at Bireuen Almuslim University in Aceh Province and students carried out the Tri Dharma of Higher Education service in the form of technical guidance on preparing financial reports according to accounting standards for Suka Ramai Atas village officials, Wih Pesam sub-district, Bener Meriah Regency. So that errors no longer occur in managing village funds and technical reporting. The results of technical guidance provide knowledge and skills to village officials by being able to record transactions and bookkeeping, especially for preparing village budget realization reports (LRA).